Integrated Business Foundation Strategy Model: A Phenomenological Study of Value-Based Strategic Alignment in Indonesian Green Textile Industry - Wijaya Ng (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study develops and validates the integrated business foundation strategy model through a phenomenological approach in the context of value-based strategic alignment. Using a phenomenological design with purposive sampling, this research explores how the 5S character foundations (Satya, Drishti, Shakti, Sangha, Samvedana) in the integrated business foundation strategy framework mediate business-IT strategic alignment. Data were collected through in-depth interviews with 12 key informants, 120 hours of participatory observation, and document analysis during February 2020 - December 2024. Data analysis employed interpretative phenomenological analysis with an intercoder reliability of 0.87. The findings reveal that the 5S integrated business foundation strategy model constructs function as strategic alignment catalysts through the character-strategy alignment effect mechanism. Analysis shows vertical alignment between Drishti (eco-friendly vision) and IT infrastructure increased energy efficiency by 25%, while horizontal alignment based on Sangha (collaboration) reduced coordination costs by 30%. This study provides significant theoretical contributions through the development of an empirically validated integrated business foundation strategy model, character-strategy alignment effect concept as a mediation mechanism, and value-based strategic alignment framework in the context of the Indonesian green industry.